The Association between Hospital-level Obstetric Quality Indicators and Maternal and Neonatal Morbidity - Howell, Elizabeth A. (JAMA, 2014)
IMPORTANCE: In an effort to improve the quality of care, several obstetric-specific quality measures are now monitored and publically reported. The extent to which these measures are associated with maternal and neonatal morbidity is not known. OBJECTIVE: To examine whether 2 Joint Commission obstetric quality indicators are associated with maternal and neonatal morbidity. DESIGN, SETTING, AND PARTICIPANTS: Population-based observational study using linked 2010 New York City discharge and birth certificate datasets. All delivery hospitalizations were identified and two perinatal quality measures were calculated. Published algorithms were used to identify severe maternal morbidity (delivery associated with a life threatening complication or performance of a life-saving procedure) and morbidity in non-anomalous term newborns (births associated with complications such as birth trauma, hypoxia, and prolonged length of stay). Mixed-effects logistic regression models were used to examine the association between maternal morbidity, neonatal morbidity, and hospital-level quality measures while risk-adjusting for patient sociodemographic and clinical characteristics. EXPOSURE: Two Joint Commission perinatal quality measures: 1) elective (non-medically indicated) deliveries at >= 37 and < 39 weeks of gestation and 2) cesarean delivery performed in low-risk mothers. MAIN OUTCOMES AND MEASURES: Individual and hospital level maternal and neonatal morbidity. RESULTS: Severe maternal morbidity occurred among 2.4% of 115,742 deliveries and neonatal morbidity occurred among 7.8% of 103,416 non-anomalous term newborns. Rates for elective deliveries performed before 39 weeks of gestation ranged from: 15.5 to 41.9 per 100 deliveries among 41 hospitals. There were 11.7 to 39.3 cesareans per 100 deliveries performed in low-risk mothers. Overall maternal morbidity ranged from 0.9 to 5.7 mothers with complications per 100 deliveries and 3.1 to 21.3 neonates with complications per 100 deliveries. The maternal quality indicators elective delivery before 39 weeks of gestation and cesarean delivery performed in low-risk mothers were not associated with severe maternal complications (RR, 1.00; 95% CI: 0.98–1.02 and RR, 0.99, 95% CI: 0.96–1.01, respectively) or neonatal morbidity (RR, 0.99; 95% CI: 0.97–1.01 and RR, 1.01, 95% CI: 0.99–1.03, respectively). CONCLUSIONS AND RELEVANCE: Rates for the quality indicators elective delivery before 39 weeks of gestation and cesarean delivery performed in low risk mothers varied widely in New York City hospitals as did maternal and neonatal complications rates. However, there were no correlations between the quality indicator rates and maternal and neonatal morbidity. Current quality indicators may not be sufficiently comprehensive for guiding quality improvement in obstetric care.